2010
DOI: 10.1007/s10549-010-0986-9
|View full text |Cite
|
Sign up to set email alerts
|

“Overcoming breast cancer drug resistance with mTOR inhibitors”. Could it be a myth or a real possibility in the short-term future?

Abstract: The mTOR pathway is pivotal not only in tumorigenesis but also in chemotherapy and hormonal drug sensitivity. It is clear that improvements in using new targeted therapies are required to improve breast cancer (BC) outcome. Nevertheless, to achieve this, new molecular biomarkers are required to define the potential sensitivity or resistance of cancer cells. By targeting the mTOR pathway, several critical central transduction pathways that sustain breast cancer are abrogated (HER-2/Neu and the estrogen receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…These findings provide clinical rationale for enhancing or extending endocrine sensitivity by combining endocrine therapy with a targeted agent against compensatory pathways. The PI3K/AKT/mTOR pathway is a crucial mediator of tumor progression [5,6,7]. As the PI3K/Akt/mTOR pathway is heavily deregulated in breast cancer [8,9], inhibitors of mTOR are of interest as potential therapeutic agents for breast cancer patients, with everolimus and temsirolimus being the key drugs considered (S1 Table).…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide clinical rationale for enhancing or extending endocrine sensitivity by combining endocrine therapy with a targeted agent against compensatory pathways. The PI3K/AKT/mTOR pathway is a crucial mediator of tumor progression [5,6,7]. As the PI3K/Akt/mTOR pathway is heavily deregulated in breast cancer [8,9], inhibitors of mTOR are of interest as potential therapeutic agents for breast cancer patients, with everolimus and temsirolimus being the key drugs considered (S1 Table).…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in OS (30.9 vs. 25.1 months) for patients receiving TDM-1 was also detected [24]. One of the mechanisms of resistance to trastuzumab is an increase in activation of the PI3K/AKT/mTOR pathway [25]. In vitro studies showed that mTOR activation was related to HER2 overexpression and responsible for HER2-positive breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…2) [8]. It has been postulated that the use of mTOR inhibitors in breast cancer may be twofold: in patients with acquired resistance, they could be used to partially restore sensitivity and provide an additional treatment period for drugs such as trastuzumab or aromatase inhibitors, whereas in patients who have not previously been treated with endocrine therapies, they could be used in combination with hormonal treatments to delay the onset of resistance and prolong treatment [5,9]. …”
Section: Rationale For Using Mtor Inhibitors In Breast Cancermentioning
confidence: 99%